2005
DOI: 10.1242/jcs.02346
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding EGF-like growth factor accelerates keratinocyte migration and skin wound healing

Abstract: Members of the epidermal growth factor (EGF) family are the most important growth factors involved in epithelialization during cutaneous wound healing. Heparin-binding EGF-like growth factor (HB-EGF), a member of the EGF family, is thought to play an important role in skin wound healing. To investigate the in vivo function of HB-EGF in skin wound healing, we generated keratinocyte-specific HB-EGF-deficient mice using Cre/loxP technology in combination with the keratin 5 promoter. Studies of wound healing revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
201
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(219 citation statements)
references
References 36 publications
15
201
0
1
Order By: Relevance
“…Indeed, several lines of evidence point to a fundamental role for HB-EGF in cell proliferation and tumorigenesis (Miyamoto et al, 2006). However, no hypoplastic abnormalities have been found in HB-EGF null mice to date; rather, HB-EGF null mice exhibit hyperplastic abnormalities Jackson et al, 2003;Yamazaki et al, 2003;Iwamoto and Mekada, 2006) as well as defects in cell migration (Mine et al, 2005;Shirakata et al, 2005). These findings suggest that HB-EGF may not function as a growth factor in developmental and physiological processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several lines of evidence point to a fundamental role for HB-EGF in cell proliferation and tumorigenesis (Miyamoto et al, 2006). However, no hypoplastic abnormalities have been found in HB-EGF null mice to date; rather, HB-EGF null mice exhibit hyperplastic abnormalities Jackson et al, 2003;Yamazaki et al, 2003;Iwamoto and Mekada, 2006) as well as defects in cell migration (Mine et al, 2005;Shirakata et al, 2005). These findings suggest that HB-EGF may not function as a growth factor in developmental and physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, analyses of HB-EGF null mice have shown that HB-EGF is a crucial factor for proper heart development and function Jackson et al, 2003;Yamazaki et al, 2003;Iwamoto and Mekada, 2006), eyelid development (Mine et al, 2005), skin wounding healing (Shirakata et al, 2005), and skin hyperplasia . Notably, HB-EGF has been suggested to be involved in proper lung development, as HB-EGF null newborns exhibit saccular wall thickening, a decrease in the number of sacculi, and the immature differentiation of type II epithelial cells .…”
Section: Introductionmentioning
confidence: 99%
“…(21) HB-EGF gene expression has been demonstrated in a variety of tissues, predominantly the lung, heart, brain and skeletal muscle. (22) HB-EGF participates in a variety of physiological and pathological processes, (11) including wound healing, (23) eyelid formation, (24) blastocyst implantation, (25) retinoic acid-induced epidermal hyperplasia (26) and atherosclerosis. (27) Recently, HB-EGF knockout mice have been established.…”
Section: Structure and Physiological Functions Of Hb-egfmentioning
confidence: 99%
“…(52) In eyelid formation in the mouse embryo and skin wound healing, HB-EGF plays a role in cell motility, but not in cell proliferation. (23,24) In MDCK cells, expression of sHB-EGF, but not non-cleavable proHB-EGF, increases cell migration, decreases cell-matrix and cell-cell interactions and promotes the development of long unbranched tubular structures, suggesting that proHB-EGF, and sHB-EGF give rise to distinct effects on cell-cell and cell-extracellular matrix interactions. (53) It has been shown that HB-EGF binds to N-arginine dibasic convertase, a metalloendopeptidase of the M16 family, and that N-arginine dibasic convertase is expressed on the cell surface of MDA-MB451 cells, where it modulates HB-EGF-induced cell migration.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…The variable v3 domain of CD44 protein harbors attachment site for heparan sulfate GAG [32], whereas dermatan/chondroitin sulfate GAG decorate invariable N-terminal domain [3]. Attachment of GAGs was demonstrated to enhance the presentation of growth factors, including heparinbinding growth factor [33], and this mechanism is important during certain physiological and disease processes including control of dermatoporosis (chronologic skin aging) [34][35][36], wound healing [37], keratinocyte migration [37] and tumor development and metastasis [38,39]. Despite its relatively low level of transcription, CD44v2-3,9-10 was up-regulated by PMA, in the presence of high calcium, by FCS, EGF and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%